2018
DOI: 10.1007/s00535-018-1480-0
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta-analysis: real-world effectiveness and safety of vedolizumab in patients with inflammatory bowel disease

Abstract: BackgroundSelective patient recruitment can produce discrepancies between clinical trial results and real-world effectiveness.MethodsA systematic literature review and meta-analysis were conducted to assess vedolizumab real-world effectiveness and safety in patients with ulcerative colitis (UC) or Crohn’s disease (CD). MEDLINE, MEDLINE In-Process, EMBASE, and Cochrane databases were searched for real-world studies of vedolizumab in adult patients with UC/CD reporting clinical response, remission, corticosteroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
105
1
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(124 citation statements)
references
References 106 publications
(229 reference statements)
14
105
1
4
Order By: Relevance
“…The safety profile of vedolizumab therapy observed in our study was similar to earlier studies (GEMINI trials and real‐world cohorts) . The incidence of serious adverse events and severe infections was relatively low with 2.9 and 3.7 per 100 patient years, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…The safety profile of vedolizumab therapy observed in our study was similar to earlier studies (GEMINI trials and real‐world cohorts) . The incidence of serious adverse events and severe infections was relatively low with 2.9 and 3.7 per 100 patient years, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…1 Similar results were recently reported in a meta-analysis of observational studies with an estimated 1 year corticosteroid-free remission rate of 31% (95% confidence interval [CI] 20-45%). 2,3 These data underscore that while a substantial proportion of treatment-resistant patients respond to VDZ therapy, the majority do not. Although this circumstance is likely multifactorial, variability in VDZ pharmacokinetics (PK) is a potential explanation in some patients.…”
Section: Introductionmentioning
confidence: 86%
“…In the GEMINI 2 pivotal phase 3 clinical trial of vedolizumab (VDZ) for Crohn’s disease (CD), approximately one‐third of patients with active CD achieved corticosteroid‐free remission at week 52 . Similar results were recently reported in a meta‐analysis of observational studies with an estimated 1 year corticosteroid‐free remission rate of 31% (95% confidence interval [CI] 20‐45%) . These data underscore that while a substantial proportion of treatment‐resistant patients respond to VDZ therapy, the majority do not.…”
Section: Introductionmentioning
confidence: 99%
“…The GEMINI LTS study also revealed long-term maintenance of vedolizumab efficacy regardless of prior anti-TNFa exposure [26]. In patients who achieved remission induction after administration of vedolizumab, maintenance of remission may be improved based on the lower immunogenicity of vedolizumab [27].…”
Section: Discussionmentioning
confidence: 97%